Kapasitas Total Antioksidan dan Uji Toksisitas Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) - Rebecca Rebecca; Siufui Hendrawan (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Oxidative stress is an imbalance between the production of Reactive Oxygen Species (ROS) and antioxidants in the body. One plant that contains antioxidants is binahong leaves (Anredera cordifolia (Ten.) Steenis). To determine the compound content contained in binahong leaves, a total antioxidant capacity test and toxicity test were carried out on binahong leaves. This research used an in-vitro experimental study consisting of an antioxidant capacity test with DPPH (1.1-diphenyl-1-picrylhydrazil) and a bioassay, namely a toxicity test with the Brine Shrimp Lethality Test (BSLT) from binahong leaf extract. Extraction of binahong leaves is carried out using the maceration method using methanol solvent and then evaporated to obtain the extract. The total antioxidant capacity test was carried out using the Blois method, the Brine Shrimp Lethality Test (BSLT) toxicity test using the Meyer method. In the antioxidant capacity test, the IC50 value was 284.199 μg/mL, which means that the antioxidant capacity of binahong leaf extract is relatively low. In the toxicity test, the LC50 was obtained at 302.25 μg/mL, which means that binahong leaf extract has a level of toxicity against (Artemia salina L.) shrimp larvae. So it can be concluded that binahong leaf extract has relatively low antioxidant capacity and has toxic properties which are thought to have antimitotic properties.